Rare Malaria Case in Jakarta: Diagnostic Challenges and Treatment Strategies for General Practitioners in Non-Endemic Area - Andrean, Melvin; Faizi Assafah, Afif (Pelopor Publikasi Akademika, 2025)
Malaria, a significant global health issue caused by Plasmodium species, is rare in urban areas like Jakarta but remains endemic in regions such as Papua, Indonesia. This case report highlights a mixed Plasmodium infection (P. vivax and P. malariae) in a 27-year-old male presenting with fever, chills, and body aches. Initially misdiagnosed with dengue fever due to overlapping symptoms, further history revealed recent travel to Papua, leading to malaria diagnosis via blood smear examination. The case emphasizes diagnostic challenges in non-endemic regions where general practitioners may lack familiarity with malaria, especially in atypical presentations. Rapid diagnostic tests, hematological markers, and detailed travel histories are critical for improving diagnostic accuracy. Treatment with dihydroartemisinin-piperaquine and primaquine was effective, showcasing the importance of adhering to national malaria guidelines. This report highlights the need for heightened awareness, better training, and improved diagnostic resources to manage malaria in non-endemic urban areas effectively.